If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3x + 1 + 8x = 2x + 5 + 4x + -3 Reorder the terms: 1 + 2x + -3x + 8x = 2x + 5 + 4x + -3 Combine like terms: 2x + -3x = -1x 1 + -1x + 8x = 2x + 5 + 4x + -3 Combine like terms: -1x + 8x = 7x 1 + 7x = 2x + 5 + 4x + -3 Reorder the terms: 1 + 7x = 5 + -3 + 2x + 4x Combine like terms: 5 + -3 = 2 1 + 7x = 2 + 2x + 4x Combine like terms: 2x + 4x = 6x 1 + 7x = 2 + 6x Solving 1 + 7x = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 7x + -6x = 2 + 6x + -6x Combine like terms: 7x + -6x = 1x 1 + 1x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + 1x = 2 + 0 1 + 1x = 2 Add '-1' to each side of the equation. 1 + -1 + 1x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 2 + -1 1x = 2 + -1 Combine like terms: 2 + -1 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| (x-5)(x).5=42 | | 6-8x=3-9x | | 4x+18=14x-62 | | (3x+5)(8x-2)=(3x)(8x)+(3x)(-2)+(5)(8x)+(5)(-2) | | 9x+28=4x+103 | | 49-3x=8x+19 | | 2x+3y-5z=1 | | 6x-5=8+5x | | 5x+4=4x+4 | | X+7=34 | | 2x+10=4x-4 | | 408=10x+22 | | 3(y+6)-y=2(y-9) | | 2(5-x)=4x | | (2x+5)(4x-2)=(2x)(4x) | | (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 | | 5x^2-6x+4=0 | | 3a+8=20 | | 2a+9=17 | | a+1=4 | | X(3)=12 | | 16x-8y=64 |